2-Oxo-2H-chromen-7-yl 3-methylbutanoate - Akoun Abou; Hypolite Bazié; Ludovic Akonan; Abdoulaye Djandé; Pierre Francotte (IUCrData)
The title compound, C14H14O4, was synthesized by O-acylation of umbelliferone with isovaleryl chloride in the presence of diethyl ether as a solvent and pyridine as a base. The side chain moiety i.e. the acetate fragment linking to the methylethyl group is almost orthogonal to the almost planar (r.m.s deviation = 0.020 Å) coumarin ring system, making an angle of 76.26 (7)°. In the crystal, the molecules form centrosymmetric dimers through pairwise C—H...O hydrogen bonds, generating R22(8) and R22(18) loops that lie within the crystallographic ac plane and propagate along the [001] direction.